Studies on improving fruit set following hand pollination in Hevea brasiliensis (Willd. ex. Adr. de Juss.) Muell. Arg. - Mydin K K; Annamma Y; Licy J; Nazeer M A; Panikkar A O N (Indian Journal of Natural Rubber Research, 1989)
An attempt was made to increase fruit set following hand pollination in Hevea. Nine treatments comprising modifications of the conventional hand pollination produced and methods to supplement nutrients and growth regulators were imposed during three flowering seasons. Enclosing particles in butter paper covers suitable size following hand pollination was found to give significantly high final fruit set than the conventional method of sealing hand pollinated flowers siginificantly high final fruit set than the conventional method of sealing hand pollinated flowers with cotton wool and latex. The effect of different treatments on fruit set has been discussed.
Keywords: Fruit set; Hand pollination; Hevea